Canada’s mental health trends: Prescription for psychology - Renner, John; Renner, Vivia (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
If you’re one of the rare, 400 individuals in the world who function as psychologists in one of Canada’s 1,423 hospitals, you’ve probably earned the right to skip over the rest of the following paragraph dealing with the basics of Canada’s mental health services. For our non-Canadian readers: Canada has a population o f approximately 22 million. The southern portion of this second-largest country in the world is divided into 10 provinces, each with its own government, but ultimately subordinate to the federal government. The northernmost, least populated, part of Canada is divided into the Northwest and Yukon territories and is administered solely by the federal government.